Development of 4D Printed PLA Actuators (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Four-dimensional (4D) printing is currently in the early stages of development and is deficient in offering designers and researchers the freedom to develop 4D printable structures. The first step to ensuring the use of such technology by researchers requires additional testing and simulation for 4D printing. It also requires an assessment of the shape memory effect in the materials that are being printed. This paper tests 4D printed actuators that possess an induced strain following printing. The induced strain is achieved during the printing process following fused deposition modelling. The induced strain permits alteration of the shape after material stimulation following printing, which eliminates the requirement for a separate programming step where alterations are required for force and stimulation to achieve the print shape temporarily. The proposed approach consists of two actuators and a drug delivery application via an open-sided box reservoir. The process of printing and shape change of polylactic acid is completed and the level of bending of actuators is then measured. The printing of designs is done at 10 mm/s for passive layers and 60 mm/s speed for active layers. The heating of the printed samples is done, and the bending angle is measured for the replication process through simulation. Finite element analysis (FEA) of the actuators is done to replicate the strain-induced through the use of materials demonstrating thermal expansion. The FEA parameters are utilized to develop intricate structures and simulate the change of the shape. The deformation values achieved by Designs 1 and 2 in the z-axis are 7.81 mm and 6.06 mm, respectively, and 4.84 mm for the reservoir.